Effect of atrial fibrillation on atrial thrombogenesis in humans: impact of rate and rhythm - Lim, Han S; Willoughby, Scott R; Schultz, Carlee; Gan, Cheryl; Alasady, Muayad; Lau, Dennis H; Leong, Darryl P; Brooks, Anthony G; Young, Glenn D; Kistler, Peter M; Kalman, Jonathan M; Worthley, Matthew I; et al. (Journal of the American College of Cardiology, 2013)
We sought to assess the effect of atrial fibrillation (AF) on atrial thrombogenesis in humans by determining the impact of rate and rhythm. Although AF is known to increase the risk of thromboembolic stroke from the left atrium (LA), the exact mechanisms remain poorly understood. We studied 55 patients with AF who underwent catheter ablation while in sinus rhythm; 20 patients were induced into AF, 20 patients were atrial paced at 150 beats/min, and 15 were control patients. Blood samples were taken from the LA, right atrium, and femoral vein at baseline and at 15 min in all 3 groups. Platelet activation (P-selectin) was measured by flow cytometry. Thrombin generation (thrombin-antithrombin [TAT] complex), endothelial dysfunction (asymmetric dimethylarginine [ADMA]), and platelet-derived inflammation (soluble CD40 ligand [sCD40L]) were measured using enzyme-linked immunosorbent assay. Platelet activation increased significantly in both the AF (p < 0.001) and pacing (p < 0.05) groups, but decreased in control patients (p < 0.001). Thrombin generation increased specifically in the LA compared with the periphery in both the AF (p < 0.01) and pacing (p < 0.01) groups, but decreased in control patients (p < 0.001). With AF, ADMA (p < 0.01) and sCD40L (p < 0.001) levels increased significantly at all sites, but were unchanged with pacing (ADMA, p = 0.5; sCD40L, p = 0.8) or in control patients (ADMA, p = 0.6; sCD40L, p = 0.9). Rapid atrial rates and AF in humans both result in increased platelet activation and thrombin generation. Prothrombotic activation occurs to a greater extent in the human LA compared with systemic circulation. AF additionally induces endothelial dysfunction and inflammation. These findings suggest that although rapid atrial rates increase the thrombogenic risk, AF may further potentiate this risk.